The Impact of Tropical Storms on Households: Evidence from Panel Data on Consumption. (15th July 2019) - Henry, Michael; Spencer, Nekeisha; Strobl, Eric
Abstract: This paper investigates the impact of tropical storms on Jamaican household consumption. We build a panel data set that follows individual households over time thus enabling us to take account of time invariant household and location unobservables that could be correlated with mean tropical storm exposure. Our results show that while the average damaging hurricane reduces per capita consumption by approximately 1.1%, more destructive events can cause losses multiple times this amount. There are, however, heterogeneous impacts across households, where only those that live in buildings with less wind resistant walls are affected. Additionally, we find that households are able to partially buffer the negative impact on consumption through remittances and savings, as well as by shifting funds away from non‐regular expenditures. Again, households differ in the nature of this buffering according to the wind resistance of their buildings.